Challenges in Educational Reform: An Experiment on Active Learning in Mathematics - Samuel G. Berlinski; Matías Busso (Inter-American Development Bank (IDB), 2015)
This paper reports the results of an experiment with secondary school students designed to improve their ability to reason, argument, and communicate using mathematics. These goals are at the core of many educational reforms. A structured pedagogical intervention was created that fostered a more active role of students in the classroom. The intervention was implemented with high fidelity and was internally valid. Students in the control group learned significantly more than those who received treatment. A framework to interpret this result is provided in which learning is the result of student-teacher interaction. The quality of such interaction deteriorated during the intervention.
hdl:11319/6825
Keywords: C93; I21; I28; O32; 330; Education Active learning; Curricular reform; Technology; Field experiments